CORROSION RESISTANCE OF MILD STEEL WELDED JOINTS: ELECTROCHEMICAL ANALYSIS IN FIVE DIFFERENT ENVIRONMENTAL MEDIA (Nigerian Journal of Technology, 2025)
This study investigates the corrosion behavior of mild steel welded joints exposed to various environmental media to evaluate their performance and durability in diverse real-world settings. The chosen environments—1M H2SO4, 1M NaCl, 1M NaOH, soil, and freshwater—represent a range of corrosive conditions from highly acidic and saline to basic and neutral, simulating scenarios that mild steel structures may encounter in industrial, marine, and natural environments. Welded joints were fabricated using optimized welding parameters and subjected to corrosion evaluation through electrochemical impedance spectroscopy (EIS), and potentiodynamic polarization tests. The results revealed that 1M H2SO4 caused the highest corrosion rate at 11.31 mm/yr and a corrosion current (Icorr) of 972.42 μA/cm², while freshwater exhibited the lowest corrosion rate of 1.55 mm/yr and an Icorr of 132.87 μA/cm². These findings underscore the significant influence of environmental conditions on the corrosion behavior of welded steel joints. The study recommends the use of advanced protective coatings or alternative materials for structures in highly corrosive environments.